Modal Sosial dan Keberlanjutan Kelembagaan dalam Program CSR PT Tirta Investama di Kabupaten Cianjur Jawa Barat - Chintia Chintia; Fredian Tonny Nasdian (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2017)
Corporate social responsibility is a responsibility that must be implemented by the company to the public and the environment. Social capital, especially social networks have a role in the sustainability of institutions in Cianjur District, West Java. The main objective is create a sustainable program, that keep continued even though the company is no longer or not directly involed. This study aims to describe social networks, social capital, institutional sustainability, and analyze the correllation between social networks and institutional sustainability. This study uses quantitative approach with census method supported by qualitative data. The results showed that the level of social networking contained in HIPOCI were on a broad level and the level of institutional sustainability in high level. Based on the research that has been tested statistically show that there is a correlattion between the level of social networking with the level of institutional sustainability.Key words: social networks, typology, correlation--------------------------ABSTRAKCSR atau tanggung jawab sosial perusahaan merupakan bentuk tanggung jawab yang wajib dilaksanakan oleh perusahaan kepada masyarakat dan lingkungan sekitar. Modal sosial, khususnya jejaring sosial memiliki peranan dalam keberlanjutan kelembagaan di Kabupaten Cianjur, Jawa Barat. Hal ini diharapkan mampu menjadikan suatu program dapat berkelanjutan meskipun perusahan tidak lagi ikut terlibat. Penelitian ini bertujuan untuk memaparkan jejaring sosial, modal sosial, keberlanjutan kelembagaan, menganalisis hubungan jejaring sosial dan keberlanjutan kelembagaan. Penelitian ini menggunakan pendekatan kuantitatif didukung data kualitatif dengan metode sensus. Hasil penelitian menunjukkan tingkat jejaring sosial yang terdapat pada HIPOCI berada di tingkat luas dan tingkat keberlanjutan kelembagaan di tingkat tinggi. Berdasarkan hasil uji secara statistik menunjukkan bahwa terdapat hubungan antara tingkat jejaring sosial dengan tingkat keberlanjutan kelembagaan.Kata kunci: jejaring sosial, tipologi, korelasi